1996
DOI: 10.1080/009841096161780
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Toxicity of Mercury, Cadmium, and Copper Toward the Isolated Perfused Rat Liver

Abstract: The toxic effects of cadmium, mercury, and copper were compared over the over range 0.01, 0.03, and 0.1 mM using the isolated perfused rat liver preparation. All metals caused similar changes in various parameters used to describe general toxicity. Thus reductions in oxygen consumption, perfusion flow, and biliary secretion were found, while lactate dehydrogenase release into the perfusate, as well as liver weight, increased also in a dose-dependent fashion. Each metal caused similar magnitudes of changes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 32 publications
3
24
1
Order By: Relevance
“…In groups with LPS, similar to groups without LPS in time-dependent manner, levels of ALT and AST increased at AFB1 concentrations of 0.01, 0.1 and 1 ppm, that concentrations of 0.1 and 1ppm had statistically significant different with LPS group. Our finding is consistent with the most investigators finding about time course of enzyme changes in exposure with naproxen [15], copper and AFB1 [16][17][18], cadmium [19], vanadium [20] in perfused rat liver model.…”
Section: Discussionsupporting
confidence: 82%
“…In groups with LPS, similar to groups without LPS in time-dependent manner, levels of ALT and AST increased at AFB1 concentrations of 0.01, 0.1 and 1 ppm, that concentrations of 0.1 and 1ppm had statistically significant different with LPS group. Our finding is consistent with the most investigators finding about time course of enzyme changes in exposure with naproxen [15], copper and AFB1 [16][17][18], cadmium [19], vanadium [20] in perfused rat liver model.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, lipid peroxidation increases mitochondrial and cellular permeability alterations, involving GSH [37,70] and calcium depletion [70]. These outcomes work together to create a continuous cycle where acceleration of the mitochondrial chain induces oxidative stress, lipid peroxidation and depletion of antioxidant defenses, which, in turn, diminish membrane permeability and accelerate the respiratory chain, thus generating more ROS.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to report in vivo protective effects of trolox on arsenic-induced hepatotoxicity, although several studies have demonstrated its efficacy in preventing toxicity of other metals. 36 In addition, studies have shown that a trolox derivative (U-83836E) appeared to be beneficial in reducing lipid peroxidation products and in partially preventing the decrease in glutathione and antioxidant enzymes induced by methanol in liver, serum 37 and brains 38 of rats. Lower doses of trolox than used in the present study clearly reduced methylmercury-induced toxicity in rats.…”
Section: Discussionmentioning
confidence: 99%